Improving Stagonospora nodorum Resistance in Wheat: A Review. Issue 2 (1st March 2013) - Francki, Michael G.
ABSTRACT: Stagonospora nodorum blotch (SNB) is a significant fungal disease of bread wheat ( Triticum aestivum L.) caused by Stagonospora nodorum, in which reduced grain yield is caused when the pathogen infects flag leaves and glumes at the critical time of grain filling. Wheat breeding programs have made limited progress in improving resistance to SNB due to the underlying complexity of the pathogen, host resistance, and their interactions. There has been an increase in knowledge of components of host–pathogen interactions in the past five decades, including pathogen diversity, biological factors contributing toward pathogen infection, environmental conditions favoring disease progression, and the genetics of host resistance. This review captures major outcomes and assesses different approaches and methodologies for improving resistance to SNB. The review concludes by proposing strategies for deploying, selecting, and combining gene and trait combinations in genetic backgrounds and improving methods for evaluation and selection of SNB resistance in wheat breeding.